2020
DOI: 10.3126/egn.v2i1.27457
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Following Decompressive Surgery for Malignant Middle Cerebral Artery Infarction

Abstract: Background and purpose: When >50% of the brain supplied by middle cerebral artery (MCA) gets infracted they are often termed as malignant MCA infarction. Decompressive hemicraniectomy has became the standard treatment option in carefully selected cases with higher survival benefit (78% Vs 29%) in a pooled analysis of one year follow up; however, there was no promising outcome noted in terms of disability rating. To see the outcome following decompressive hemicraniectomy and lax duroplasty for malignant midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This value could help the neurosurgeon in the setting of emergency craniotomy or elective craniotomies in the absence of Neuronavigation for proper placement of burrs and craniotome to prevent sinus injury. 11,12 In the literature the safety limit of placement of burr hole is somewhere around 15 mm from the midline sagittal suture; however, as for the finding in our study the burr hole placed 25 mm to the right and 20 mm to the left seems necessary to prevent sinus injury in all cases of craniotomy around superior sagittal sinus because even a small dural tear over the lateral limits of sinus will also lead to devastating bleeding or air embolism. 13 Dural venous sinus seems to make a groove in the inner table of the skull bone and it corresponds to the size of the sinus but it doesn't seem to grow or shrink with the advancing age.…”
Section: Figure 2: Distribution Of Gendermentioning
confidence: 49%
“…This value could help the neurosurgeon in the setting of emergency craniotomy or elective craniotomies in the absence of Neuronavigation for proper placement of burrs and craniotome to prevent sinus injury. 11,12 In the literature the safety limit of placement of burr hole is somewhere around 15 mm from the midline sagittal suture; however, as for the finding in our study the burr hole placed 25 mm to the right and 20 mm to the left seems necessary to prevent sinus injury in all cases of craniotomy around superior sagittal sinus because even a small dural tear over the lateral limits of sinus will also lead to devastating bleeding or air embolism. 13 Dural venous sinus seems to make a groove in the inner table of the skull bone and it corresponds to the size of the sinus but it doesn't seem to grow or shrink with the advancing age.…”
Section: Figure 2: Distribution Of Gendermentioning
confidence: 49%
“…Thirty-four studies reported the mean age of the patient population [ 10 , 12 – 14 , 19 23 , 26 28 , 30 , 31 , 33 , 36 – 41 , 45 , 48 , 50 – 53 , 56 , 57 , 59 , 60 , 62 – 64 ]. As indicated in Table 1 , the pooled mean age was 62.4 years, ranging from 51.9 [ 38 ] to 70.5 years [ 18 ]. From 46 studies reporting data on sex distribution, 44 studies showed a higher percentage of stroke in males [ 10 , 12 – 14 , 16 , 19 – 21 , 23 28 , 30 – 33 , 35 – 41 , 43 45 , 47 51 , 53 – 59 , 61 – 64 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…From 23 studies investigating aspects of acute care [ 13 , 30 , 40 , 49 ], four studies consisted of data on length of hospital stay [ 13 , 30 , 40 , 49 ], four studies highlighted complications [ 13 , 16 , 30 , 48 ], and 19 studies reported mortality [ 11 , 17 , 21 , 26 , 29 , 30 , 32 , 34 , 36 , 38 , 40 , 41 , 45 , 48 , 51 , 52 , 56 , 57 , 62 ]. 12 studies included treatment modalities [ 21 , 31 , 32 , 36 , 38 , 42 45 , 48 , 57 , 61 ] [ 42 , 44 , 61 ].The outcome of stroke was described in 22 studies [ 11 , 17 , 21 , 26 , 29 , 30 , 32 34 , 36 , 38 , 40 , 41 , 43 45 , 48 , 51 , 52 , 56 , 57 , 62 ], and the long-term outcome (3 months after stroke) was investigated only in seven studie...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…raniotomy is the most common procedure done in neurosurgical patients. [1][2][3][4] During a craniotomy, there is a high chance of unintentional dural tear which is attached to the skull bone. 2,5,6 Dural tear may occur in both layers or only in the outer layer.…”
mentioning
confidence: 99%